Analisis Kualitas Pelayanan Publik dengan Metode Fuzzy-Service Quality (F-Servqual) dan Index Potential Gain Customer Value (IPGCV) - Wahyu Oktri Widyarto; Nugraheni Djamal; Fauzul Adhim (Universitas Serang Raya, 2018)
This study aims to analyze the level of service quality and prioritize improvements. The method that used in this study is service quality (SERVQUAL) combined with fuzzy concepts to find out the gap between expectations and consumer perceptions through five dimensions namely tangible, reliability, responsiveness, assurance, and empathy. Fuzzy concepts are used to present uncertainties over respondents' assessment of subjective questionnaires. To determine the priority of improvement, used the Customer Value Index Potential Gains (IPGCV) method. Based on processing data results by using fuzzy-servqual method, it is known that the Tangible dimension has a gap of -0.13, the Reliability dimension has a gap of -0.13, the Responsive dimension has a gap of -0.14, the dimension of Assurance has a gap of -0.12, Empathy dimension has a gap of -0.11. The negative value on fuzzy-servqual assessment can be interpreted that the overall service has not met customer expectations. Achievement of the quality level is equal to 0.8606 which is indicates the quality of services still need improvement because the level of service quality is less than 1. Based on calculation using the PGCV Index, it is known that services which have the highest priority are employees who have adequate support from their institutions so that they can carry out their duties properl